ENHANCING ACADEMIC WRITING SKILLS THROUGH PODCAST CREATION: A QUALITATIVE CASE STUDY OF EFL STUDENTS AT SRIWIJAYA UNIVERSITY - Tamara Shelvy Maharani; Rita Inderawati; Hamdi Akhsan; Tita Ratna Wulan Dari (English Review: Journal of English Education, 2025)
This qualitative case study focused on examining scientific article writing process. Scientific article writing is a crucial skill for university students, yet it is often taught through conventional approaches that do not fully engage learners. To encourage more interactive learning, the English Education Study Program at Sriwijaya University introduced a podcast project in the Article Writing course. This study employed a qualitative case study design, drawing data from student podcast transcripts and questionnaires. Findings showed that while all groups completed the brainstorming stage, many struggled to advance with drafting, revising, and editing, and none discussed publishing. Students most frequently addressed the Introduction and Conclusion, while the Theoretical Overview and Literature Synthesis were less developed. In terms of language features, academic vocabulary was used most consistently, with partial strengths in grammar, coherence and cohesion, and clarity and precision. However, students demonstrated weaknesses in referencing style and objectivity, and no evidence of hedging or formal tone was found. The main challenges reported were teamwork, technical barriers, and time management. These findings suggest that podcasts can serve as effective learning media for academic writing if supported by structured guidance in revision and publication, strengthened academic literacy, and systematic technical and project management support.